La historia de las ciencias y la enseñanza : una selección bibliográfica - Navarro Brotons, Víctor (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A bibliographical list, which is not meant to be exhaustive, is presented, being thought as usefull to know the role of the History of Sciences in teaching.